ANALISIS KEMAMPUAN PESERTA DIDIK DALAM MENYELESAIKAN TES HIGHER ORDER THINKING SKILL (HOTS) BERBANTUAN APLIKASI WINSTEP TENTANG MATERI PESAWAT SEDERHANA KELAS VIII SMP NEGERI 3 PONTIANAK - Syarif Novan Al Fajar; Stepanus Sahala Sitompul; Syaiful B. Arsyid (Jurnal Inovasi Penelitian dan Pembelajaran Fisika, 2022)
This study aims to determine the level of thinking skills of students in solving Higher Order Thinking Skill (HOTS) questions about simple aircraft material which are then analyzed with the help of the winstep program from Rasch modeling. This research is a descriptive qualitative research with a survey method. Data collection by giving a test, HOTS-based questions with cognitive levels C4 and C5 as many as 15 items in multiple choice form. Subjects in this study amounted to 120 students that is all students of class VIII SMP Negeri 3 Pontianak. Based on data analysis, it can be concluded that the average level of thinking ability of students in solving HOTS questions about simple aircraft material is 59% in the moderate category. The level of thinking ability of students at each cognitive level can be concluded that the average thinking ability of students at the cognitive level to analyze (C4) is 50% with the medium category, and at the cognitive level evaluating (C5) by 44% with low categories. The level of thinking skills of students on each simple aircraft sub-material can be concluded that the average thinking ability of students on the lever material is 37% with the medium category, on the inclined plane material, namely 52% with the high category, and the pulley material is 35% in the low category. Based on the results of this analysis, it shows that on average students have not been able to solve questions with more complex characteristics or a high level. Therefore, This research is expected that students can be trained in solving problems at a higher level in accordance with the demands of the 2013 curriculum.